Budesonide Loaded PLGA Nanoparticles for Targeting the Inflamed Intestinal Mucosa-Pharmaceutical Characterization and Fluorescence Imaging - Ali, Hussain; Weigmann, Benno; Collnot, Eva-Maria; Khan, Saeed Ahmad; Windbergs, Maike; Lehr, Claus-Michael (Pharmaceutical Research, 2016)
The purpose of this study was to evaluate the specifically targeted efficiency of budesonide loaded PLGA nanoparticles for the treatment of inflammatory bowel disease (IBD).The nanoparticles were prepared by an oil/water (O/W) emulsion evaporation technique. The nanoparticles were characterized for their size, shape and in vitro drug release profile. Solid state characterization was carried out by differential scanning calorimetry (DSC) and X-ray Power diffraction (XPRD). In order to evaluate the targeted efficiency of nanoparticles, a particle localization study in the healthy and in the inflamed colon was determined in vivo. These data were complemented by cryo-sections.Nanoparticles were 200 ± 05 nm in size with a smooth and spherical shape. The encapsulation efficiency was around 85 ± 3.5%, which was find-out by both, direct and indirect methods. Release of budesonide from the nanoparticles showed a biphasic release profile with an initial burst followed by sustained release. XPRD data revealed that the drug in the polymer matrix existed in crystalline state. Nanoparticles accumulation in inflamed tissues was evaluated by in-vivo imaging system and it was found that particles are accumulated in abundance at the site of inflammation when compared to the healthy group.The study demonstrates that the budesonide loaded PLGA nanoparticles are an efficient delivery system for targeted drug delivery to the inflamed intestinal mucosa.
EVALuna2:2106